The role of networks and clusters in rural development - Micskei, Péter (Acta Agraria Debreceniensis, 2010)
The development of rural areas is a key role for the European Union and its member states as well. The rural development primarily achieved through the development of agriculture, because the main beneficiaries of the grant are the farmers. Hungary today is close to 1 million units in agriculture, but only 10% are competitive. Agriculture as an industry according to its economic characteristics needs closely managed decentralization, where the autonomy of the units remain, but there is a central governing body, which constitutes a proffesional manager function. This is a superorganization, which stay above agricultural units, called cluster.